2021
DOI: 10.3390/insects12050447
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of the Gypsy Moth Lymantria dispar (Lepidoptera: Erebidae) to Nosema pyrausta (Microsporidia: Nosematidae)

Abstract: The gypsy moth, Lymantria dispar, is a notorious forest defoliator, and various pathogens are known to act as natural regulators of its population density. As a widespread herbivore with a broad range of inhabited areas and host plants, it is potentially exposed to parasitic microorganisms from other insect hosts. In the present paper, we determined the susceptibility of gypsy moth larvae to the microsporidium Nosema pyrausta from the European corn borer, Ostrinia nubilalis. Gypsy moth samples from two localit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The microsporidian isolate from the cotton bollworm showed 100 % identity to the previously characterized isolate from the same host and location, sampled two years earlier (Kononchuk et al, 2021). When compared to other Genbankaccessible entries, it also showed a high level of sequence correspondence of the diagnostic DNA fragments to those of the known species.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The microsporidian isolate from the cotton bollworm showed 100 % identity to the previously characterized isolate from the same host and location, sampled two years earlier (Kononchuk et al, 2021). When compared to other Genbankaccessible entries, it also showed a high level of sequence correspondence of the diagnostic DNA fragments to those of the known species.…”
Section: Resultsmentioning
confidence: 59%
“…In 2019, a novel isolate was found in a population of cotton bollworms Helicoverpa armigera (Hübner 1808). Comparison of SSUrDNA fragments of this isolate with the orthologs of other representatives of the genus Nosema suggested identity or very close relationships of the isolated microsporidium to N. bombycis (Kononchuk et al, 2021). Due to similarity of the spore structure and low sequence divergence of rRNA genes among Nosema spp., differentiation of species within this group poses a serious problem (Kyei-Poku et al, 2008;Issi et al, 2020;Tokarev et al, 2020).…”
Section: Discussionmentioning
confidence: 84%
“…Attempts to propagate N. pyrausta in substitute laboratory hosts, such as the greater wax moth, Galleria mellonella (Linnaeus, 1758) (Pyraloidea: Pyralidae) (Tokarev et al, 2018), and the gypsy moth, Lymantria dispar (Linnaeus, 1758) (Noctuoidea: Erebidae) (Kononchuk et al, 2021), were reported. Those, however, significantly lower as compared to +24 °C (Welch's test, P = 0.006).…”
Section: Discussionmentioning
confidence: 99%
“…The observed microsporidian infection level is rather unusual for L. dispar in Western Siberia, i.e., in the Asian part of L. dispar's geographic range [36]. Microsporidia were not detected in recent surveys of L. dispar in Western Siberia [37] and this prevalent microsporidian infection was quite unexpected. According to our observations, the most prevalent pathogen in Siberian L. dispar populations is LdMNPV [36].…”
Section: Discussionmentioning
confidence: 99%